Endurance exercise and the risk of cardiovascular pathology in men: a comparison between lifelong and late-onset endurance training and a non-athletic lifestyle - rationale and design of the Master@Heart study, a prospective cohort trial. Issue 2 (16th April 2021) - De Bosscher, Ruben; Dausin, Christophe; Claus, Piet; Bogaert, Jan; Dymarkowski, Steven; Goetschalckx, Kaatje; Ghekiere, Olivier; Belmans, Ann; Van De Heyning, Caroline M; Van Herck, Paul; Paelinck, Bernard; El Addouli, Haroun; et al.
Abstract : Introduction: Low and moderate endurance exercise is associated with better control of cardiovascular risk factors, a decreased risk of coronary artery disease and atrial fibrillation (AF). There is, however, a growing proportion of individuals regularly performing strenuous and prolonged endurance exercise in which the health benefits have been challenged. Higher doses of endurance exercise have been associated with a greater coronary atherosclerotic plaque burden, risk of AF and myocardial fibrosis (MF). Methods and analysis: Master@Heart is a multicentre prospective cohort study aiming to assess the incidence of coronary atherosclerosis, AF and MF in lifelong endurance athletes compared to late-onset endurance athletes (initiation of regular endurance exercise after the age of 30 years) and healthy non-athletes. The primary endpoint is the incidence of mixed coronary plaques. Secondary endpoints include coronary calcium scores, coronary stenosis >50%, the prevalence of calcified and soft plaques and AF and MF presence. Tertiary endpoints include ventricular arrhythmias, left and right ventricular function at rest and during exercise, arterial stiffness and carotid artery intima media thickness. Two hundred male lifelong athletes, 200 late-onset athletes and 200 healthy non-athletes aged 45–70 will undergo comprehensive cardiovascular phenotyping using CT, coronary angiography, echocardiography, cardiac MRI, 12-lead ECG, exercise ECG and 24-hour Holter monitoring at baseline. Follow-up will include online tracking of sports activities, telephone calls to assess clinical events and a 7-day ECG recording after 1 year. Ethics and dissemination: Local ethics committees approved the Master@Heart study. The trial was launched on 18 October 2018, recruitment is complete and inclusions are ongoing. Trial registration number: NCT03711539 .